The WHO 2018 Classification of Cutaneous Melanocytic Neoplasms: Suggestions From Routine Practice - Ferrara, Gerardo; Argenziano, Giuseppe (Frontiers in Oncology, 2021)
The ‘multidimensional’ World Health Organization (WHO) classification 2018 of melanocytic tumors encompasses 9 melanoma pathways (7 of which for cutaneous melanoma), according to a progression model in which morphologically intermediate melanocytic tumors are cosidered as simulators and/or precursors to melanoma. These “intermediates” can be subclassified into: i) a ‘classical’ subgroup (superficial/thin compound: dysplastic nevus), which is placed within the morphologic and molecular progression spectrum of classical (Clark’s and McGovern’s) melanoma subtypes (superficial spreading and, possibly, nodular); and ii) a ‘non-classical’ subgroup (thick compound/dermal: ‘melanocytomas’) whose genetic pathways diverge from classical melanoma subtypes. Such a progression model is aimed at giving a conceptual framework for a histopathological classification; however, routine clinicopathological practice strongly suggests that most melanomas arise de novo and that the vast majority of nevi are clinically stable or even involuting over time. Clinicopathological correlation can help identify some severely atypical but benign tumors (e.g.: sclerosing nevus with pseudomelanomatous features) as well as some deceptively bland melanomas (e.g.: lentiginous melanoma; nested melanoma), thereby addressing some ambiguous cases to a correct clinical management. The recently available adjuvant therapy regimens for melanoma raise the problem of a careful distinction between severely atypical (high grade) melanocytoma and ‘classical’ melanoma: conventional morphology can guide an algorithmic approach based on an antibody panel (anti mutated BRAF, BAP1, PRAME, ALK, TRKA, MET, HRAS-WT, ROS; beta catenin; R1alpha; p16; HMB45; Ki67), a first-line molecular study (identification of hot spot mutations of BRAF and NRAS), and an advanced molecular study (sequencing of NF1, KIT, BRAF, MAP2K1, GNAQ, GNA11, PLCB4, CYSLTR2, HRAS; fusions studies of BRAF, RET, MAP3K8, PRKCA); as a final step, next-generation sequencing can identify melanocytic tumors with rare genetic signatures and melanocytic tumors with a high tumor mutation burden which should be definitely ascribed to the category of classical melanoma with the respective therapeutic options.